VICTIMS AND PERPETRATORS IN CYBERBULLYING - MOISE, Adrian-Cristian (International Journal of Legal and Social Order, 2022)
Starting from the definition and the framework that regulates the phenomenon of cyberbullying, the article aimed to present and analyze the main aspects related to the victims and criminals involved in this phenomenon. Cyberbullying refers to illegal actions that intentionally and repeatedly cause harm to minors through new technologies. The article analyzes issues related to the motivation and typology of criminals, the impact of the cyberbullying phenomenon among victims and the causes of this illegal behaviour.